Legal Cost Insurance as a Strategic Device in Settlement Negotiations - Roland Kirstein (Universität des Saarlandes, Center for the Study of Law and Economics (CSLE), 1999)
The papers show that Legal Cost Insurance (LCI) is a device to enhance potential litigants' bargaining position rather than to re-allocate risk. Being insured decreases the cost an insured party has to bear if settlement negotiations fail and the case goes to trial. This shifts the threat points, which has an impact on the bargaining result. In negative expected value suits, LCI can make the threat to sue credible and motivate potential defendants to make positive settlement offers. Hence, even risk-neutral agents may find it beneficial to insure. – – Diese beiden Diskussionspapiere zeigen, daß Rechtsschutzversicherungen eher ein Mittel zur Positionsverbesserung bei Vergleichsverhandlungen als ein Mittel der Risiko-Reallokation sind. Die Versicherung senkt die Kosten, die im Falle des Scheiterns der Vergelcihsverhandlungen und eines Prozesses noch zu tragen wären. Hierdurch verschiebt sich der Drohpunkt und damit auch das Vergleichsergebnis. In Fällen mit negativem Erwartungswert kann die Versicherung sogar die Klagedrohung glaubwürdig machen und den Beklagten überhaupt zu einem positiven Vergleichsergebnis motivieren. Dadurch ist eine Rechtsschutzversicherung auch für risikoneutrale Akteure interessant.
Keywords: K41; G22; 330; Civil Procedure; Bargaining; Settlement; Negative Expected Value Suits